PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP LEVERAGE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DAN KIMIA SUB SEKTOR LOGAM DAN SEJENISNYA YANG TERDAFTARDI BURSA EFEK INDONESIA TAHUN 2016-2018 - Yuni Efnita; Rahmawati Rahmawati (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted with the aim to examine the effect of liquidity and profitability on leverage and variables that influence leverage on industrial manufacturing companies and chemical sub-sector metals listed on the Indonesia stock exchange in 2016-2018. The population in this study are all industrial and chemical manufacturing companies listed on the Indonesia stock exchange in the 2016-2018 period. The technique used in sampling is the purposive sampling method, the samples in this study were selected as many as 16 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneous liquidity and profitability affected leverage. Partially, liquidity (CR) affects the leverage.